Phytol-Derived Novel Isoprenoid Immunostimulants - Chowdhury, Roshni R.; Ghosh, Swapan K. (Frontiers in Immunology, 2012)
This review describes the adjuvanticity of novel diterpenoids (synthetic phytol derivatives) compared to some commercially available adjuvants. The efficacy of the phytol-derived immunostimulants was evaluated in terms of their ability to activate innate immunity, amplify various antigen-specific immune responses and engender immunological memory with no discernible adverse effects in both competent and immune-deficient mice. The profile that emerges out of these studies reveals that the phytol derivatives are excellent immunostimulants, superior in many respects to a number of commercial adjuvants.